HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU BULLYING PADA SISWA SMA AL-AZHAR 3 BANDAR LAMPUNG TAHUN 2019 - Muhammad Odis Nursyhabudin; Hetti Rusmini; Supriyati Supriyati; Nina Herlina (PSIKOLOGI KONSELING, 2021)
Bullying cases that often occur in the world of education in Indonesia are increasingly alarming. The impact of bullying can cause a child who is a victim to be hampered in self-actualization. There are several factors that influence bullying behavior, one of which is parenting style or parenting. The purpose of this research was to determine the correlation between parenting style with bullying behavior in high school students.This type of research is a descriptive observational analytic method using the Cros Sectional design. The sample in this study was that all students of class XII Natural Sciences / Social Sciences at Al-Azhar 3 Bandar Lampung High School were 176 students. Data obtained through filling the bullying behavior scale consists of 29 items and the parenting scale consists of 30 items. Data analysis technique to test the hypothesis is Anova One Way. The results showed that most of the respondents with democratic parenting were 113 respondents (64.2%), the majority of respondents with low bullying behavior were 119 respondents (67.6%) and there was a relationship between parenting patterns with bullying behavior in SMA AL-AZHAR 3 students in Bandar Lampung (p value 0,000). The research showed a correlation between parenting style with behavior bullying in senior high school students of Al-Azhar 3 Bandar Lampung 2019.